2020
DOI: 10.4136/ambi-agua.2578
|View full text |Cite
|
Sign up to set email alerts
|

Use of organic fertilization with irrigation in coffee production in brazilian cerrado

Abstract: Coffee irrigation has increased in the main Brazilian coffee regions. However, in recent years, with climate change, years with water deficits greater than 150 mm have been observed, affecting the vegetative and productive development of the crop and also the replenishment of surface and underground springs. One practice that increases soil water retention capacity is organic fertilization. This work evaluated different combinations of irrigation and organic fertilization on the yield and quality of coffee pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…e result of this study was also in line with several research findings [39][40][41][42][43][44][45][46][47], which conveyed that the application of organic fertilizer, particularly vermicompost, improved plant heights. Similar findings were also explored by Maru et al [48]; Sikder and Joardar [49]; and Bhattarai et al [50], who determined that the application of organic fertilizer in biochar form increased plant height in pea and rice crops.…”
Section: Plant Height (Cm)supporting
confidence: 90%
“…e result of this study was also in line with several research findings [39][40][41][42][43][44][45][46][47], which conveyed that the application of organic fertilizer, particularly vermicompost, improved plant heights. Similar findings were also explored by Maru et al [48]; Sikder and Joardar [49]; and Bhattarai et al [50], who determined that the application of organic fertilizer in biochar form increased plant height in pea and rice crops.…”
Section: Plant Height (Cm)supporting
confidence: 90%
“…This study's outcome also agreed with several other research outputs [ 2 , 4 , 5 , 32 , 34 , [44] , [45] , [46] , [47] , [48] , [49] ] who generally and concisely reported that taller plant heights were observed when grown using organic amendments such as forest soil, decomposed coffee husk, farmyard manure, vermicompost, animal and plant biochar etc. This could be because of a huge amount of organic matter and total nitrogen present [ 15 , 17 , 19 , 50 ] which enhance the capacity to easily uptake nutrients [ 42 , 51 ], maintain soil moisture and enhance soil fertility [ 52 , 53 ] that ultimately improves growth media porosity, aeration and water retention capacity [ 54 ].…”
Section: Resultssupporting
confidence: 89%
“…2 ). Likewise, the number of true leaves was declined when the ratios of organic amendments reduced in the growth media compositions supported by Castillo and Andrade [ 5 ], Letort et al [ 72 ], Fernandes et al [ 45 ] and Hirpa [ 47 ]. This could be also due to the photosynthetically active radiation and solar brightness [ 3 , 5 , 73 ] as the leaf is responsible for evapotranspiration, nutrient and water use, carbon assimilation, development rate, and photosynthetic efficiency [ 74 ].…”
Section: Resultsmentioning
confidence: 72%
“…It is the most important genus in economic terms, mainly due to the species Coffea arabica L. (Martins, 2012;Agler et al, 2016). Brazil has adopted intensive agricultural practices to meet the demand for coffee consumption in many countries; this practice includes heavy use of chemical fertilizers, a variety of chemical treatments to fight pests, and combined plants (herbicides), all with adverse effects and impact on the environment (Fernandes et al, 2020;Loftfield et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Organic agriculture is an alternative that can benefit consumers, farmers, and the environment by eliminating harmful chemicals (Ferdous et al, 2021). The legitimately organic coffee production concept is based on agricultural management similar to an organism's life, respecting the agricultural property's productive potential (Craheix et al, 2016;Fernandes et al, 2020).…”
Section: Introductionmentioning
confidence: 99%